Pengaruh Pelaksanaan Good Governance terhadap Pelayanan Publik pada Kantor Desa Barangmamase Kecamatan Sajoanging - Riska Amaliah; Jamal Qadar; najeminur najeminur (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Improving the quality of public services is one of the key objectives in village governance. To achieve this goal, the implementation of good governance principles is highly relevant, as it ensures that services are delivered in a transparent, accountable, responsive, and citizen-oriented manner. This study aims to analyze the influence of good governance on the quality of public services at the Barangmamase Village Office, Sajanging District, Wajo Regency. The research employed a census method by involving the entire population as the research sample. Data collection techniques included observation, questionnaires, and documentation, while the data analysis technique applied was descriptive analysis to illustrate the actual conditions in the field. The findings indicate that the implementation of good governance, according to respondents, is categorized as good, and the quality of public services is also categorized as good. Furthermore, quantitative analysis shows that good governance has a strong and positive influence on public service delivery. This implies that the better the implementation of good governance principles, the higher the level of public satisfaction with the services provided. The study emphasizes the importance of consistently applying the principles of transparency, accountability, participation, and effectiveness to improve the quality of public services at the village level. These findings are expected to serve as a useful reference for village governments and future researchers in developing further studies on the relationship between governance practices and community satisfaction in the context of public service delivery.